Curbing Hatred: The Ethnic Diehards' Agitations and 2015 Presidential Election Campaign in Nigeria - Abigail Odozi Ogwezzy-Ndisika (Journal of Hate Studies, 2019)
Nigeria witnessed bouts of hate speeches during the buildup to the March 28, 2015 Presidential election. Politicians and their allies made use of acerbic words, half-truths and outright lies during their electioneering campaigns. The election was regarded as a do-or-die affair by the politicians. Their activities were alarming and apprehensions were rife about the success of the election and peaceful transition of power. Hence, the two major contestants, Goodluck Jonathan and Muhammadu Buhari along with nine party leaders signed the Abuja Accord on January 14, 2015. Furthermore, the country experienced a season of acerbic comments, issuance of quit notices and calls for secessions by ethnic jingoists. These activities heated up the polity and caused panic among the citizens of the country. On June 6, 2017, the Arewa Youth Consultative Forum comprising of 19 Northern states of Nigeria issued a 90-day ultimatum to South-Eastern residents in the North to vacate the region before October 1, 2017. This article explores the use of hate speech in electioneering campaign drawing from secondary data i.e. newspaper excerpts; and through the lens of ethics using relevant Communication Practice Codes, Nigerian Press Council Code, Nigerian Broadcasting Code, 2012 and relevant sections of Electoral Act 2010. It also examines the issue of the ethnic diehards agitations and quit notice and its implications for national peace, security and justice. The argument and submission of this paper highlights ways of curbing hatred, advancing of peace, acceptance, tolerance and justice.